Transaksi Non Tunai dalam Perspektif Hadis: Antara Inovasi Digital dan Prinsip Syariah - Diva Pinara; Muhammad Alif; Repa Hudan Lisalam (Al-Mu'tabar, 2025)
The advancement of digital technology has significantly transformed economic transaction systems, including the widespread use of non-cash payment methods such as e-wallets, mobile banking, and QR codes. This article aims to examine the phenomenon of non-cash transactions from the perspective of the Prophet Muhammad’s hadiths, focusing on the integration between digital innovation and Islamic legal principles. The study employs a qualitative method with a thematic approach to hadiths related to justice, honesty, the prohibition of gharar (ambiguity), riba (usury), and trustworthiness in financial dealings. The findings reveal that although non-cash transactions are not explicitly addressed in classical hadith literature, the ethical values contained in the hadiths provide a normative framework relevant to assessing the legitimacy and appropriateness of modern digital financial systems. When understood contextually, non-cash transactions can be accepted in Islam as long as they uphold transparency, fairness, and avoid prohibited elements. This article underscores the importance of applying the maq??id al-shar?‘ah approach to evaluating modern economic innovations in order to maintain harmony between technological development and Islamic values.